2022
DOI: 10.3390/biomedicines10020323
|View full text |Cite
|
Sign up to set email alerts
|

Histologic-Based Tumor-Associated Immune Cells Status in Clear Cell Renal Cell Carcinoma Correlates with Gene Signatures Related to Cancer Immunity and Clinical Outcomes

Abstract: The three-tier immunophenotype (desert, excluded, and inflamed) and the four-tier immunophenotype (cold, immunosuppressed, excluded, and hot) have been linked to prognosis and immunotherapy response. This study aims to evaluate whether immunophenotypes of clear cell renal cell carcinoma, identified on hematoxylin and eosin-stained slides, correlate with gene expression signatures related to cancer immunity, and clinical outcomes. We evaluated tumor-associated immune cells (TAICs) status using three methodologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…In this setting, our findings combining transcriptome and histology data, although with their own limitations, carry an element of novelty and contribute to the understanding of the tissue-specific immune contexture in melanoma. Our definition of desert, excluded, and inflamed immune subtypes is aligned with related reports on other cancer types, such as ovarian [14,51,52], lung [53][54][55], head and neck, [52,56,57] breast [55,58], bladder [52,53], gastric [52], colorectal [52], hepatocellular [59], pancreatic [60], and renal cancer [61], and contributes to developing agreement on universal immune contexture elements among different cancer localizations.…”
Section: Discussionsupporting
confidence: 60%
“…In this setting, our findings combining transcriptome and histology data, although with their own limitations, carry an element of novelty and contribute to the understanding of the tissue-specific immune contexture in melanoma. Our definition of desert, excluded, and inflamed immune subtypes is aligned with related reports on other cancer types, such as ovarian [14,51,52], lung [53][54][55], head and neck, [52,56,57] breast [55,58], bladder [52,53], gastric [52], colorectal [52], hepatocellular [59], pancreatic [60], and renal cancer [61], and contributes to developing agreement on universal immune contexture elements among different cancer localizations.…”
Section: Discussionsupporting
confidence: 60%
“…As an essential component of immunotherapy, analysis of the tumor immune microenvironment (TIME) contributes to prediction of responsiveness to immunotherapy. Promising clinical results have been achieved in a variety of cancers by reprogramming the immunosuppressed state in tumors to an immune activated state ( 24 ). In our study, we explored the relationship between riskScore and immune cells in TIME and found that the high-risk group displayed a more abundant macrophage infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has identi ed the immunotherapy as a promising intervention for cancer patients [11]. By reprograming the immunosuppressive state in the "cold tumor" into an activated one, the usage of immune checkpoint inhibitors as well as some cell-speci c compounds has achieved exciting clinic outcome in multiple cancers [12,13]. However, immunotherapy in CC remain largely unexplored.…”
Section: Introductionmentioning
confidence: 99%